고령인구의 거주지 인지도 특성에 관한 연구 - 권순정; 정다운; 오예인 (의료·복지 건축, 2018)
Purpose: This study was conducted to figure out the cognitive characteristics of the elderly living in apartment complex in order to construct basic data for the design of sustainable and age friendly apartment area. Methods: Cognitive map was used to identify and analyze the elderly residents’ status of residential environment cognitions. The elderly living in Gongreung-dong apartment was randomly interviewed outdoor area and requested to draw cognitive maps on their living environment. 26 valid cognitive maps collected were analyzed, classified into two different types: Line type and Dot type. The average age, cognitive distance, length of residence, number of elements in the map(complexity) were then compared by Line and Dot type, as well as by gender. Correlations among variables also were analysed. Results: Males showed a tendency to draw dot types, which means they are place-centered, and females drew line types more than males, which means they are way-centered. The average cognitive distance of male group was greater than that of female group. As the age went up, the number of perceived place and the cognitive distance decreased. Oder people tended to draw line types rather than dot types. As the cognitive distance was longer, the perceived place and the number of lines increased. Implications: The age was more related to the recognition of the residential environment. The younger the residents were, the more they recognized the elements. The points that were represented by dots in the cognitive maps are places for memories for the individuals. Creating more memorable spaces will affect the cognition of residents on living environment. It is better to improve the cognitive environments before cognitive abilities of residents decrease.
Keywords: cognitive map; aging in place; apartment complex; cognitive type; 인지도; 거주지노화; 아파트단지; 인지유형